Impediments for software test automation: A systematic literature review. (5th September 2017) - Wiklund, Kristian; Eldh, Sigrid; Sundmark, Daniel; Lundqvist, Kristina
Summary: Automated software testing is a critical enabler for modern software development, where rapid feedback on the product quality is expected. To make the testing work well, it is of high importance that impediments related to test automation are prevented and removed quickly. An enabling factor for all types of improvement is to understand the nature of what is to be improved. We have performed a systematic literature review of reported impediments related to software test automation to contribute to this understanding. In this paper, we present the results from the systematic literature review: The list of identified publications, a categorization of identified impediments, and a qualitative discussion of the impediments proposing a socio‐technical system model of the use and implementation of test automation. Abstract : As a facilitator of frequent and rapid feedback, test automation is a critical part of the modern software development process. Automating software testing is thus often organizationally prioritized. However, an enabling factor for all types of improvement is to understand the nature of what is to be improved. On the basis of a systematic review of the literature, we provide a sociotechnical view of test automation and describe impediments for its use and implementation.